Accuracy and skill of the Conformal-Cubic Atmospheric model in short-range weather forecasting over Southern Africa - Rautenbach, C.J. de W. (Cornelis Johannes de Wet) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2007.